THE ROLE OF SOCIAL NETWORKS IN IMPROVING MENTAL IMAGE OF PUBLIC RELATIONS DEPARTMENT IN SERVICE INSTITUTIONS – AN APPLY STUDY ON UBER AND CAREEM COMPANIES AS A MODEL – - Ghryani, Ghofran Ahmad; Omar, Halema Alhabib Adam (Journal of Humanities & Social Sciences, 2021)
The study aimed to identify the role of social networks in the process of improving the mental image in service institutions، and to identify the methods of social marketing followed by the Department of Public Relations via social networks، and the degree of dependence on these networks and the extent of the impact of this dependence on the institution mental image. The researcher used the survey methodology to achieve the goal of the study، and she chose Uber and Careem Companies for transport services as a model for the study. The study’s sample consisted of (400) random Uber and Careem customers that represented Makkah and Madinah residents، and (30) non-random single samples of public relations practitioners in Uber and Careem. The period of time it took to apply the study’s tool extended between 01/10/2019 to 31/12/2019.The study reached to the following results: the existence of an effective relationship between the Department of Public Relations usage of social networks and the quality of its provided services، and the mental image، as both companies’ customers and public relations practitioners agreed upon. This means that the mental image is affected negatively or positively according to the services provided by Uber and Careem via social networks and the quality of such services. The results also showed that the mental image of Uber and Careem that the costumers form during the application period of the study was a positive mental image. It also proved that the provided services are affected by the customers’ formed mental image. In addition، the results proved the multiplicity of strategies and methods that the Public Relations Department relies upon to improve its mental image through social networks.A number of recommendations were presented based on the study’s results، one of these important recommendations is that the Department of Public Relations at Uber and Careem must take the social networks into consideration as the results demonstrated the ability of these networks to influence the mental image. They also have to raise the level of communication with the customers to ensure the preservation of their positive mental image. The study also recommended the importance of conducting more studies at the same subject due to the rapid development of modern means of communication.
Keywords: mental image; social networks; public relations; Uber; Kareem